Brand relevance making competitors irrelevant - Aaker, David A.; ProQuest (Firm) (San Francisco, Calif. : Jossey-Bass, 2011)
"Substantial market trends and transformational innovations are creating markets and making others irrelevant. The result is a major threat for nearly every business and a significant opportunity for a few. This book will be the first marketing strategy book to develop and leverage the concept of brand relevance. To remain relevant, a firm can create a new category or subcategory-- such as iPod, Cirque du Soleil, and eBay did-- where competitors are eliminated. Or a firm can redefine an existing category or subcategory by creating or elevating an offering feature or characteristic--as Prius created a subcategory defined by gas mileage and technology, or Westin did with its Heavenly Bed. In either case, a firm can create or own a new business arena or submarket in which some or all competitors are not relevant. Instead of being the best, the goal is to be the only--making competitors irrelevant"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Brand name products; Branding (Marketing); Technological innovations; Electronic books